Analysis of Current Routing Attacks in Mobile Ad Hoc Networks - Hande BAKILER; Aysel ŞAFAK (International Journal of Applied Methods in Electronics and Computers, 2015)
Mobile ad hoc networks (MANET) has no fixed infrastructure and depends on nodes to perform routing of data packets. MANET nodes are highly self organized even with a collection of few mobile nodes. Security is an important issue for mobile ad hoc networks. Even though mobile ad hoc networks have many advantages over the traditional wired network, when it comes to security it poses an immense set of threats. The scope of this project is to study about Misbehavior Node attack, Byzantine attack and Pulse Jammer attack on Reactive Routing Protocol i.e. Ad Hoc On Demand Distance Vector (AODV) on MANET simulation environment. To perform the simulations we used OPNET modeller 14.5 as the network simulator for our proposed work. The results showed that MANET posed a high security risk attack either from internal or from external attack.